A mutational analysis of the cytosolic domain of the tomato Cf‐9 disease‐resistance protein shows that membrane‐proximal residues are important for Avr9‐dependent necrosis - Chakrabarti, Apratim (Mol Plant Pathol, 2015)
The tomato Cf‐9 gene encodes a membrane‐anchored glycoprotein that imparts race‐specific resistance against the tomato leaf mould fungus C ladosporium fulvum in response to the avirulence protein Avr9. Although the N‐terminal half of the extracellular leucine‐rich repeat (eLRR) domain of the Cf‐9 protein determines its specificity for Avr9, the C‐terminal half, including its small cytosolic domain, is postulated to be involved in signalling. The cytosolic domain of Cf‐9 carries several residues that are potential sites for ubiquitinylation or phosphorylation, or signals for endocytic uptake. A targeted mutagenesis approach was employed to investigate the roles of these residues and cellular processes in Avr9‐dependent necrosis triggered by Cf‐9. Our results indicate that the membrane‐proximal region of the cytosolic domain of Cf‐9 plays an important role in Cf‐9‐mediated necrosis, and two amino acids within this region, a threonine (T835) and a proline (P838), are particularly important for Cf‐9 function. An alanine mutation of T835 had no effect on Cf‐9 function, but an aspartic acid mutation, which mimics phosphorylation, reduced Cf‐9 function. We therefore postulate that phosphorylation/de‐phosphorylation of T835 could act as a molecular switch to determine whether Cf‐9 is in a primed or inactive state. Yeast two‐hybrid analysis was used to show that the cytosolic domain of Cf‐9 interacts with the cytosolic domain of tomato VAP27. This interaction could be disrupted by an alanine mutation of P838, whereas interaction with CITRX remained unaffected. We therefore postulate that a proline‐induced kink in the membrane‐proximal region of the cytosolic domain of Cf‐9 may be important for interaction with VAP27, which may, in turn, be important for Cf‐9 function.